Photochemistry and electrochemistry in continuous flow toward integrated processes - DeLaney, Erica Noel (2018)
This thesis describes how continuous flow photochemical and electrochemical reactions can contribute to sustainable synthesis, particularly when coupled to on-line analysis techniques or used as part of a multi-step synthetic process. Chapter 1 introduces photochemistry as a sustainable technique, the problems that have previously been associated with performing photochemical reactions in batch, and presents the potential benefits of performing photochemistry in continuous flow. Chapter 2 describes the UV photochemical reactor that was built as part of this Thesis, which uses monochromatic excimer lamps (KrCl = 222 nm, XeBr = 282 nm, and XeCl = 308 nm) as the reaction light source. Results from two initial model reactions, the [2+2] cycloaddition of maleimide with 1-hexyne and the photo-isomerisation of β ionone are presented in addition to chemical actinometry measurements of the radiant exitance of each excimer lamp. Chapters 3 and 4 report the outcomes of two of the chemical reactions that were studied in the excimer reactor. In Chapter 3 results obtained for the photodecarboxylative cycloaddition of 4-phthalimidobuytric acid are presented, including the effects of sensitising solvent and irradiation wavelength dependence. This chapter also describes the integration of the photochemical reactor with a second acid catalysis step by performing an acid catalysed dehydration of the photoproduct. Both the photo-reaction and the dehydration were performed in flow from a single reagent steam. Chapter 4 describes the photochemical isomerisation of 2-pyridone in the continuous excimer flow reactor. Our reactor allowed for a more efficient reaction than comparable batch reactions. The conversion of starting material in this reaction was successfully monitored by in-line flow UV-Vis spectroscopy using a miniature UV-Vis spectrometer. Chapter 5 briefly introduces electrochemistry in continuous flow, which, like photochemistry, is an under utilised “reagent-less” technique that can benefit from being performed in continuous flow reactors. Specifically, the work described in Chapter 5 involved separating the hydrogen gas produced during electrochemical reactions performed in a commercially available electrochemical flow reactor, so that on-line analysis could more easily be integrated with the reactor. The methoxylation of N-formylpyrolidine was chosen as a model reaction in an attempt to incorporate in-line Raman spectroscopy with the electrochemical reactor. Secondly, the methoxylation of 4-tert-butyltoluene was used as the model reaction for assimilating the electrochemical reactor with on-line GC analysis. After separating the hydrogen gas from the reaction by a simple gravity separation, both techniques were capable of providing in/on-line analysis results. However, the GC experimental set-up proved to give better results as the reaction set-up had a smaller dead volume and therefore required less equilibration time. All relevant experimental details and reactor standard operating procedures are given in Chapter 6 with supplementary information provided where necessary in the appendices. The overall conclusions for this Thesis and recommendations for future work are collected in Chapter 7.